Pengaruh Perceived Organizational Support terhadap Organizational Citizenship Behavior dengan Job Satisfaction sebagai Variabel Mediasi pada Pegawai Dinas Koperasi dan UKM DIY - Khalyfatul Azizah; Nur Rokhman (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Abstract This study aims to examine and analyze the effect of perceived organizational support on organizational citizenship behavior with job satisfaction as a mediating variable on the employees of the Department of Cooperatives and UKM DIY. The sample in this study were civil servants and contract employees of the DIY Cooperatives and SMEs Office with a total of 44 respondents. The sampling technique uses the Saturated Sampling or Census method. The analytical method used is Path Analyze or Path Analysis. The conclusion of this study is that perceived organizational support has a not significant effect on organizational citizenship behavior, perceived organizational support has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on organizational citizenship behavior, and job satisfaction has a mediating effect on perceived organizational support on organizational citizenship behavior.